(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article intend to understand how can occur the construction of a body in art, in the possible limits between a theatrical performance and a performative action. It limits to explore this questioning through some female voices inserted in the theatrical and performative field. The main focus in the investigation of these materials was the observation of women’s body work, from their bodies on stage, aiming to a female visibility and their questions. Thus, were used as materials for analysis the piece “Tem alguém que nos odeia” – that encompasses lesbo-female representation – and the performance entitled “6 minutos” which deals with questions about abortion.